Sulfur-doped cobalt phosphide nanotube arrays for highly stable hybrid supercapacitor. (September 2017) - Elshahawy, Abdelnaby M.; Guan, Cao; Li, Xin; Zhang, Hong; Hu, Yating; Wu, Haijun; Pennycook, Stephen J.; Wang, John
Abstract: Metal phosphides are promising electrode materials for supercapacitors, owing to their conductive properties and high capacity. However, they are suffering from the short term cycling stability. Herein, an efficient sulfidisation strategy is successfully established to improve the overall electrochemical performance of metal phosphides. In detail, sulfur-doped CoP nanotube arrays aligned on carbon cloth are developed through a sulfidisation reaction process with CoP, which can provide significant improvement in electrochemical performance over that of bare CoP. The sulfur-doped CoP nanotube arrays not only show a capacity which is 1.78 times higher than that of CoP, but also demonstrate excellent cycle stability retaining 99% of the original capacity after 10, 000 charge and discharge cycles, which is much better than CoP alone. Furthermore, a hybrid supercapacitor has been fabricated using sulfur-doped CoP as the positive electrode, which can deliver a maximum energy density of 39 W h/kg at a power density of 0.8 kW/kg. The full cell also shows excellent cycling stability by maintaining 86.4% of the original capacitance after 50, 000 cycles, which is much better than previously reported metal phosphide-based supercapacitors. Graphical abstract: Novel hollow and porous sulfur-doped CoP nanotube arrays have been achieved through a facile one-step sulfidisation process, which shows much improved rate capability and long-term cycling stability. Highlights: Novel hollow sulfur-doped CoP nanotube arrays through a facile one-step sulfidation process. The sulfur-doped CoP nanotube arrays showed higher capacity and better stability than bare CoP. A hybrid supercapacitor based on Co(P, S) nanotube arrays can deliver high energy and power density.